2011
DOI: 10.1111/j.2158-1592.2011.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Logistics Service Quality (e-LSQ): Its Impact on the Customer’s Purchase Satisfaction and Retention

Abstract: The Internet retailing industry continues to grow rapidly. Several Internet retailers are, however, struggling to retain customers due to the high level of competition among incumbents. We propose that customer satisfaction with the order fulfillment process is an important determinant of overall customer satisfaction with the retailer, as well as with the extent of customer retention enjoyed by the retailer. This paper offers a new concept for electronic logistics service quality and investigates the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
166
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(192 citation statements)
references
References 69 publications
3
166
0
5
Order By: Relevance
“…Danesh et al (2012) added that a scale is reliable if alpha values above 0.7 are obtained. As shown in Table 3, the values for all items were above 0.7 as recommended (Manzoor & Naeem, 2011;Rao et al, 2011), indicated good reliability. …”
Section: Validity and Reliability Of The Instrumentmentioning
confidence: 88%
See 1 more Smart Citation
“…Danesh et al (2012) added that a scale is reliable if alpha values above 0.7 are obtained. As shown in Table 3, the values for all items were above 0.7 as recommended (Manzoor & Naeem, 2011;Rao et al, 2011), indicated good reliability. …”
Section: Validity and Reliability Of The Instrumentmentioning
confidence: 88%
“…However, Alshurideh, Masa'deh and Alkurdi (2012) and Danesh et al (2012) found that customer satisfaction has a direct effect on customer retention. Moreover, Rao, Goldsby, Griffis and Iyengar (2011) support the link between purchase satisfaction and customer retention. Based on the above literature, we propose the following hypothesis:…”
Section: Relationship Between Customer Satisfaction and Customer Retementioning
confidence: 99%
“…Likewise, Rao et al (2011) identified a strong correlation between LSQ, price of logistics service and CS. When the logistics service was not included in the final price of the product, but paid for by the customer, the price of these services had a negative influence on CS.…”
Section: Lsq and Csmentioning
confidence: 99%
“…Reliability, which ensures stability and consistency of the results, was assessed using Cronbach's alpha. According to Rao, Goldsby, Griffis and Iyengar (2011), a recommended value of alpha is 0.7 or more. The results of this test are shown in Table 1. www.ccsen Table 1.…”
Section: Validity and Reliabilitymentioning
confidence: 99%